Irrigation-dependent accumulation of microcystin in different crops under mid-scale greenhouse conditions - Wannes H.R. Van Hassel; Elise Tardy; Bart Cottyn; Mirjana Andjelkovic; An Decombel; Jeroen Van Wichelen; Julien Masquelier; Andreja Rajkovic (Journal of Agriculture and Food Research)
The potential health risks of consuming crops irrigated with microcystin-contaminated water are increasingly recognized. While previous studies demonstrated microcystin accumulation in crops, they do not fully reflect real-world conditions and have data gaps. Moreover, some available studies also obtained data with suboptimal analytical methods.Therefore, this study evaluated microcystin-LR (MC-LR) accumulation in strawberries, carrots, and lettuce under spray and drip irrigation, using a state-of-the-art, validated UHPLC-MS/MS method in a medium-scale setup similar to commercial greenhouse production.MC-LR was detected in the outer and middle leaves of lettuce after spray irrigation. In carrots, only a few replicates showed MC-LR in the greens or taproot, yielding inconclusive results. In strawberries, MC-LR accumulated in the roots, foliage, and fruit after spray irrigation. Additionally, drip irrigation led to MC-LR accumulation in strawberry roots and greens, even though only the roots were directly exposed.The findings suggest that strawberry plants are particularly susceptible to microcystin accumulation when irrigated with contaminated water, highlighting the need for risk mitigation measures.